2015
DOI: 10.1159/000373888
|View full text |Cite
|
Sign up to set email alerts
|

Gonadotropin Therapy versus Laparoscopic Ovarian Drilling in Clomiphene Citrate-Resistant Polycystic Ovary Syndrome Patients: A Retrospective Cost-Effectiveness Analysis

Abstract: Background: Gonadotropin therapy and laparoscopic ovarian drilling (LOD) are treatment options for ovulation induction (OI) in clomiphene citrate (CC)-resistant polycystic ovary syndrome (PCOS) patients. The current evidence of the cost-effectiveness of both treatments is scarce, conflicting and performed from different health-economic perspectives. Methods: A retrospective health-economic evaluation was performed from a societal perspective in which human menopausal gonadotropin (hMG) therapy (n = 43) was com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…7 In another study, Begum showed the mean age was 22.67±6.3 years varied from 18 to 35 years and Codner et al found mean age was 24.5±5.0 years varied from 19 to 40 years which are less than the current study. 15 Summed ovarian volume (cm 3 ) were found between responders and non-responders after LOD. A systematic review Badawy et al and Elmashad concluded that ovarian volume has little clinical application in prediction of poor pregnancy response.…”
Section: Resultsmentioning
confidence: 94%
“…7 In another study, Begum showed the mean age was 22.67±6.3 years varied from 18 to 35 years and Codner et al found mean age was 24.5±5.0 years varied from 19 to 40 years which are less than the current study. 15 Summed ovarian volume (cm 3 ) were found between responders and non-responders after LOD. A systematic review Badawy et al and Elmashad concluded that ovarian volume has little clinical application in prediction of poor pregnancy response.…”
Section: Resultsmentioning
confidence: 94%
“…The societal cost per patient, up to an ongoing pregnancy, was significantly higher after LOD versus hMG treatment (adjusted mean difference EUR 1073, 95 % CI 180-1967). This economic evaluation based on real-life data shows that the societal cost up to an ongoing pregnancy is less after hMG treatment when compared with LOD surgery in CC-resistant PCOS patients [10].…”
Section: Discussionmentioning
confidence: 92%
“…A retrospective health-economic evaluation was performed from a societal perspective in which human menopausal gonadotropin (hMG) therapy (n = 43) was compared with LOD (n = 35), followed by OI with CC and/or hMG if spontaneous ovulation did not occur within 2 months [10]. Data were collected until the patients were pregnant, with a time limit of 6 months after the onset of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, De Frene et al compared the pregnancy rates of 43 women in whom ovulation was induced with human menopausal gonadotropin and 35 who were treated via LOD; the ongoing pregnancy rates were similar (60% and 69.8%, respectively). 20 Also, Bayram and colleagues reported a pregnancy rate of 49% of women treated with clomiphene citrate/electrocautery and 67% in those given recombinant FSH, in a randomized controlled trial. 21 In a study of PCOS patients resistant to clomiphene citrate, Goudarzi and co-workers reported similar pregnancy rates in LOD groups and groups in whom ovulation was induced with gonadotropins (OR: 0.534; 95% CI: 0.242-1.176; p=0.119; six studies, n=499, I 2 =73.201%).…”
Section: Discussionmentioning
confidence: 99%